Distilling contributions of administrative law in promoting the culture of good governance - Singh, S.S. (1998)
Visualising primacy of administrative law in promoting good governance, the author first presents the fundamental features of administrative law which are congruent to realisation of good governance. He then, drawing heavily from values in administrative law, discusses the measures needed to realise good governance. He, in fact, also suggests certain reforms in administrative law itself to further secure effects of good governance in public administration. - Reproduced
Keywords: Public administration; Administrative law; Good governance